Térelválasztó bútor tervezése - Sulyok Dorisz (2015)
Abstract In my thesis I designed a partition furniture. First I collected the modern partition designs, than I made a summary what kind of functions they have. After I wrote the function tree I choosed the most important functions and some additional functions for a designing guideline. The best idea was the „VaryCube”. This furniture project is made of cubic parts, and it is really variable. The desk and the chairs could be hidden in the cube parts. It has also got some additional panels, which can hang on the cubes with magnets. It was designed for small apartments, but it also fits in every modern rooms. The main idea came from my apartment, where I had no place for the dining chairs. I have an american kitchen, but when my chairs are not in use, they are absolutely in my way in the kitchen. I designed this furniture, so I could hide my chairs after use, and I would have more space in the kitchen. At the same time I would have a partition between the kitchen and the living room. The furniture is made of pine wood, and the chairs are upholstered. The parts are mounted, and it is really easy to assembly them. I designed it for international markets, that is why it has got english fantasy name and slogan. The slogan is “As you like it!” which comes from a drama title of the famous writer William Shakespeare.